P48 Vitamin D Levels Are Not Associated with Markers of Inflammation and Disease Severity in Acute Tuberculosis. (19th November 2012) - Perrin, FM; Togun, E; Stephens, S; Sewo, O; Barker, RD
Abstract : Background: There is considerable evidence that patients with clinical tuberculosis in the UK have low levels of circulating Vitamin D 1 . It has been suggested that acquired Vitamin D deficiency impairs immune function and therefore allows patients to transform from latent to clinical tuberculosis. Sceptics have suggested that the low Vitamin D levels seen in clinical tuberculosis are a result of disease activity rather than a cause of it. We examined whether Vitamin D levels were associated with blood markers of inflammation and disease severity inpatients newly diagnosed with tuberculosis. Methods: All patients diagnosed with tuberculosis at an inner London teaching hospital since 2000 were eligible for inclusion in the study although systematic measurement of Vitamin D levels has only been attempted in recent years. Vitamin D levels were classified as deficient <=10ng/ml, insufficient>10 to <30ng/ml and sufficient >=30ng/ml.2 The date treatment started was recorded. The first blood measurement of Vitamin D, Haemoglobin, Neutrophil count, c-reactive protein(CRP), erythrocyte sedimentation rate (ESR) and albumin taken within two weeks of treatment starting were recorded. All variables were assessed for correlation with one another using Pearson's correlation coefficient in SPSS. Results: One thousand four hundred and twenty two patients were identified of whom 262 had a measurement of Vitamin D. 151 (58%) were Vitamin D deficient and a further 96 (37%), Vitamin D insufficient. Data availability ranged from 1266 patients with a serum albumin to 222 patients with an ESR. Blood markers of disease severity and inflammation were significantly correlated but Vitamin D levels did not correlate with any of the other variables. Discussion: These data do not support the hypothesis that low Vitamin Dlevels in acute tuberculosis are a result of disease activity or severity. It would be reasonable to consider the prevention of Vitamin D deficiency as a means to reduce the conversion of latent to clinical tuberculosis. References: Sita-Lumsden A, Lapthorn G, Swaminathan R, Milburn HJ. Reactivation of tuberculosis and vitamin D deficiency: the contribution of diet and exposure to sunlight. Thorax 2007; 62(11):1003–7. Rosen CJ. Vitamin D Insufficiency. New EnglandJournal of Medicine 2011; 364(3):248–54.